Managing patients with tuberculosis and HIV infection : methodical recommendations for self-study for practical classes of students of higher medical education of the 5th year of study in the discipline "Phthisiology" - Poteiko, P.I.; Hrek, I.I.; Konstantynovska, O.S.; Volobuieva, O.V.; Lyadova, T.I.; Kushnir, V.B.; Потейко, Петро Іванович; Грек, Іван Ігорович; Константиновська, Ольга Сергіївна; Кушнір, Василь Борисович; Лядова, Тетяна Іванівна; Волобуєва, Ольга Вікторівна (Kharkiv : V. N. Karazin Kharkiv National University, 2024)
The methodical recommendations were developed by the team of teachers of the Department of General and Clinical Immunology and Allergology of the Medical Faculty of V.N. Karazin Kharkiv National University. An indicative map of the work of candidates for higher medical education is provided, which clearly defines, consistently and in detaildescr ibes the recommendations for preparation at each stage of practical teaching. The list of basic theoretical issues and practical skills, structure and content of the subject, test tasks for control of initial and final level of knowledge, basic and additional literature, the appendices contain links to electronic resources of educational materials of the department.

В останні роки в Україні одночасно розвиваються епідемії двох соціально небезпечних хвороб – туберкульозу і ВІЛ/СНІДу, що часто уражають одні й ті ж групи населення. Туберкульоз, як найбільш розповсюджене опортуністичне захворювання, став головною причиною захворюваності і смертності у хворих на СНІД. Серед ВІЛ-інфікованих та хворих на СНІД найрозповсюдженішою опортуністичною інфекцією є туберкульоз. ВІЛ-інфекція підвищує ризик активного туберкульозу і, навпаки, туберкульоз несприятливо впливає на перебіг ВІЛ-інфекції. Методичні рекомендації створені для вивчення особливостей діагностики ко-інфекції туберкульоз/ВІЛ, їх взаємовпливу на перебіг і прогноз лікування обох захворювань, навчання здобувачів вищої медичної освіти 5-го року сучасній тактиці ведення хворих з ко-інфекцією ТБ/ВІЛ.
Ведення хворих на туберкульоз у поєднанні з ВІЛ-інфекцією (aнгл. мовою)
Keywords: MEDICINE::Internal medicine::Lung diseases; tuberculosis; HIV; treatment; comorbidity; management; туберкульоз; ВІЛ; лікування; коморбідність; ведення